Dwarf peach trees induced by budding on japanese apricot - Dall'Orto, Fernando Antonio Campo; Ojima, Mário; Barbosa, Wilson; Martins, Fernando Picarelli (Pesquisa Agropecuaria Brasileira, 1992)
Researches are being carried out on the use of japanese apricot (Prunus x Mume, Sieb. & Zucc.), as a new rootstock for propagation of peach trees with compact and dwarf crowns, for a high density planting (higher than 1,600 plants/ha), for an increase of production/area, and for making management of cultural practices easier. The results of burble budding from 27 cultivars and of IAC peach (including nectarine) selections on 'ACUME' (IAC-3), as well as initial observations, during three years, of the production and of the behavior of the material, are presented.